If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 2(sin) * x * 2(cos) * x Reorder the terms for easier multiplication: 0 = 2 * 2ins * x * cos * x Multiply 2 * 2 0 = 4ins * x * cos * x Multiply ins * x 0 = 4insx * cos * x Multiply insx * cos 0 = 4cinos2x * x Multiply cinos2x * x 0 = 4cinos2x2 Solving 0 = 4cinos2x2 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-4cinos2x2' to each side of the equation. 0 + -4cinos2x2 = 4cinos2x2 + -4cinos2x2 Remove the zero: -4cinos2x2 = 4cinos2x2 + -4cinos2x2 Combine like terms: 4cinos2x2 + -4cinos2x2 = 0 -4cinos2x2 = 0 Divide each side by '-4'. cinos2x2 = 0 Simplifying cinos2x2 = 0 The solution to this equation could not be determined.
| 6-x=42 | | (2u+5v)(2u-5v)= | | -28x+24-3x-12=30 | | 104x=3x+6 | | 17/2+1/2= | | 6a+3=3a+15 | | 0=2sinx*2cosx | | 2y+7x=-5 | | 2=4r+n | | 3+17+5x=7x+10 | | 99=2d-419 | | h(1)=5 | | -x^2+9x=16 | | 6(5y-8)-(4y+7)= | | 4(-7x+6)-3(x-2)=30 | | 8t^2+64=0 | | 3-2(4n-6)=5(n+4) | | -2(n+1)=0 | | X^4+20=21 | | 69+2u=-23 | | 8x-(3x-17)=52 | | 5y+2x=19 | | -2x+2=-7+17 | | 15-(-30s)=465 | | 3(x-1)4+7=19 | | 2s-3=9 | | Y=ln(1-x^2) | | Y=(18-9)*p | | x=23+9 | | 3=16x+15 | | 17-2(1-3x)4=5 | | h(-3)=-3 |